A DNA Damage-Regulated BRCT-Containing Protein, TopBP1, Is Required for Cell Survival - Yamane, Kazuhiko (American Society for Microbiology, 2002)
BRCA1 carboxyl-terminal (BRCT) motifs are present in a number of proteins involved in DNA repair and/or DNA damage-signaling pathways. Human DNA topoisomerase II binding protein 1 (TopBP1) contains eight BRCT motifs and shares sequence similarity with the fission yeast Rad4/Cut5 protein and the budding yeast DPB11 protein, both of which are required for DNA damage and/or replication checkpoint controls. We report here that TopBP1 is phosphorylated in response to DNA double-strand breaks and replication blocks. TopBP1 forms nuclear foci and localizes to the sites of DNA damage or the arrested replication forks. In response to DNA strand breaks, TopBP1 phosphorylation depends on the ataxia telangiectasia mutated protein (ATM) in vivo. However, ATM-dependent phosphorylation of TopBP1 does not appear to be required for focus formation following DNA damage. Instead, focus formation relies on one of the BRCT motifs, BRCT5, in TopBP1. Antisense Morpholino oligomers against TopBP1 greatly reduced TopBP1 expression in vivo. Similar to that of ataxia telangiectasia-related protein (ATR), Chk1, or Hus1, downregulation of TopBP1 leads to reduced cell survival, probably due to increased apoptosis. Taken together, the data presented here suggest that, like its putative counterparts in yeast species, TopBP1 may be involved in DNA damage and replication checkpoint controls.